Oral Health Care Management in Atypical Oral and Cutaneous Bullous Pemphigoid - Widowati, Kharinna; Dewanthy P, Sri; Lukisari, Cane; Nafi’ah; Setianingtyas, Dwi; Rahman, Kurnia Hayati; Libriansyah; Riyanto, Eko; Damaiyanti, Dian W; Ayuningtyas, Nurina F. (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2026)
Background: Bullous Pemphigoid (BP) is the most common subepidermal bullous autoimmune disease, typically presenting as tense bullae. Atypical presentations of bullous pemphigoid often mimic TEN or impetigo, creating diagnostic ambiguity. Effective management of these cases requires integrated strategies to address systemic health factors and extensive oral mucosal involvement. Objective: This report highlights the Oral Health Care Management of atypical oral and cutaneous manifestations of Bullous Pemphigoid. Case: A 58-year-old woman with a history of Diabetes Mellitus and heart disease was referred with extensive bullae, erosions, and